2016
DOI: 10.1097/wnr.0000000000000655
|View full text |Cite
|
Sign up to set email alerts
|

Human area 5 modulates corticospinal output during movement preparation

Abstract: Neuroimaging evidence suggests that human Brodmann area 5 (BA5) within the superior parietal lobule contributes to movement planning. However, a causal role for the contribution of BA5 to preparatory processes has yet to be reported. We used paired-pulse transcranial magnetic stimulation to investigate the influence of human BA5 on corticospinal excitability during movement preparation in the context of a GO/NO-GO task. Functional connectivity between BA5 and the ipsilateral primary motor cortex (M1) was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Also, neuroimaging experiments have identified increased neural activity in the dorsoposterior parietal cortex (at MNI coordinates close to the ones found here; Figure 1) during sustained inhibition of finger movements toward an undesired target [3]. In the same vein, dual-TMS (transcranial magnetic stimulation) protocols have revealed that a conditioning magnetic pulse delivered over the anterior part of DPPr can depress motor-evoked potentials triggered, in the first dorsal interosseous, by a test pulse delivered over the ipsilateral M1 [4,5]. Finally, and most importantly, clinical observations have shown that focal parietal injuries encompassing DPPr can cause a rare clinical condition where the hand of the patient moves ''alone'' outside his/her conscious will [6,[29][30][31].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Also, neuroimaging experiments have identified increased neural activity in the dorsoposterior parietal cortex (at MNI coordinates close to the ones found here; Figure 1) during sustained inhibition of finger movements toward an undesired target [3]. In the same vein, dual-TMS (transcranial magnetic stimulation) protocols have revealed that a conditioning magnetic pulse delivered over the anterior part of DPPr can depress motor-evoked potentials triggered, in the first dorsal interosseous, by a test pulse delivered over the ipsilateral M1 [4,5]. Finally, and most importantly, clinical observations have shown that focal parietal injuries encompassing DPPr can cause a rare clinical condition where the hand of the patient moves ''alone'' outside his/her conscious will [6,[29][30][31].…”
Section: Discussionsupporting
confidence: 76%
“…Although current models emphasize the involvement of frontal networks [1,2], indirect evidence suggests a potential contribution of the posterior parietal cortex (PPC). This region is active during inhibition of upper-limb movements to undesired targets [3], and its stimulation with single magnetic pulses can depress motor-evoked potentials [4,5]. Also, it has been speculated that alien hand movements caused by focal parietal lesions reflect a release of inhibition from PPC to M1 [6].…”
Section: Inhibition Is a Central Component Of Motor Controlmentioning
confidence: 99%
“…Some areas seem to participate to action control by increasing their facilitatory influence on the corticospinal tract. This is the case of the premotor cortex (PMC; Buch and others 2010; Davare and others 2009; Koch and others 2007) and of parietal areas of the dorsal stream such as the anterior intraparietal sulcus (Allart and others 2019, Vesia and others 2013), the superior parietal lobule (Mackenzie and others 2016), the supramarginal gyrus (Koch and others 2010), the superior parieto-occipital cortex (Allart and others 2019, Vesia and others 2013; Vesia and others 2017) and even secondary visual areas (Strigaro and others 2015; Fig. 4A, left panel).…”
Section: Circuits Tuning Corticospinal Excitability During Action Conmentioning
confidence: 99%
“…Frontal areas play a role not only in sensory attentional and spatially oriented processing, but also in working memory processing, [32][33][34] whereas parietal regions are involved in the processing of proprioceptive information, 35 reorienting 36 and recognition of a matching position during visually guided tasks, 37 and in the modulation of spinal motor output during movement preparation. 38 Another relevant and novel finding of our study is the observation of a significant increase of brain activity in patients, compared with HS, during the ipsilateral matching task. This result, in combination with the absence of significant differences in behavioral performance between the two groups for this task, suggests an efficient supplying Figure 4.…”
Section: Position Sense Deficits and Their Neural Correlates During Lmentioning
confidence: 60%